New migrants, new challenges? – Activating multilingual resources for understanding mathematics: institutional and interactional factors - Krause, Arne; Wagner, Jonas; Redder, Angelika; Prediger, Susanne (European journal of applied linguistics, 2022)
New adolescent migrants from Arabic-speaking countries face complex challenges when participating in regular mathematics classes in Germany: They have been educated in their family language(s) and are obliged to adapt to a new (second or target) language and to different styles of teaching. In contrast, 3 generation multilingual students, who usually are schooled in German only, have rarely ever used their family languages in mathematics. This poses different challenges for the introduction of multilingual teaching and learning. By comparing German-Turkish 3 generation students and adolescent refugees from Arabic speaking countries, both in 7 grade, this paper argues for the epistemic importance of considering “multilingual profiles” (i. e. including individual languages and history of migration) for linguistic analyses as well as for didactical designs of learning opportunities. For this purpose, a functional pragmatic discourse analysis of transcribed video-data from bilingual mathematics sessions with up to four multilingual students was conducted. This allows to characterize discursive multilingual profiles and to distinguish different perspectives on and verbalizations of mathematical concepts (in this case: fractions) in classroom discourse. Furthermore, language-specific interfaces of mental and linguistic processes are unfolded which enable new insights into conceptual understanding. The analysis focusses on the languages German, Turkish and Arabic and on 7 grade mathematics classes. The paper shows that the activation of multilingual resources in mathematics classrooms sets a promising approach for a sustainable integration of migrants, since they are enabled to use their subject-related knowledge which, in the long run, holds the potential support for the acquisition of the target language on a pre-academic level.